Making thermoluminescence materials Caso4: Dy3+ and determining parameters kinetics of model otor - Tran, Phú Cường; Le, Sơn Hải; Huynh, Chí Cường (Journal of Technical Education Science, 2010)
In this paper, we make up thermoluminescence of materials CaSO4: Dy3+ with methods: recrystallisation method in hot and dense H2SO4, heat method. The sample was gamma radiated by 60Co (4.8kGy) to get the thermoluminescence spectroscopy. After that, we analysed the spectroscopy by deconvolution method and other methods: thermal cleaning method, initial rise method, peak shape method, whole glow peak method. Based on these results, we have calculated the parameters of One Trap One Recombination− OTOR mode.